2019
DOI: 10.3390/molecules24224056
|View full text |Cite
|
Sign up to set email alerts
|

Cell Suspensions of Cannabis sativa (var. Futura): Effect of Elicitation on Metabolite Content and Antioxidant Activity

Abstract: Cannabis sativa L. is one of the most-studied species for its phytochemistry due to the abundance of secondary metabolites, including cannabinoids, terpenes and phenolic compounds. In the last decade, fiber-type hemp varieties have received interest for the production of many specialized secondary metabolites derived from the phenylpropanoid pathway. The interest in these molecules is due to their antioxidant activity. Since secondary metabolite synthesis occurs at a very low level in plants, the aim of this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 58 publications
(68 reference statements)
0
19
0
Order By: Relevance
“…However, cell suspension cultures may still be promising for producing other secondary metabolites such as terpenes, polyphenols, lignans, and alkaloids [ 7 , 10 ]. For instance, Gabotti et al [ 55 ] reported that the activity and expression of tyrosine aminotransferase (TAT) and phenylalanine ammonia-lyase (PAL) increased in cannabis cell suspension cultures using a methyl jasmonate elicitor in combination with tyrosine precursor. Some aromatic compounds such as 4-hydroxyphenylpyruvate (4-HPP) were also identified.…”
Section: In Vitro Culture In Cannabismentioning
confidence: 99%
“…However, cell suspension cultures may still be promising for producing other secondary metabolites such as terpenes, polyphenols, lignans, and alkaloids [ 7 , 10 ]. For instance, Gabotti et al [ 55 ] reported that the activity and expression of tyrosine aminotransferase (TAT) and phenylalanine ammonia-lyase (PAL) increased in cannabis cell suspension cultures using a methyl jasmonate elicitor in combination with tyrosine precursor. Some aromatic compounds such as 4-hydroxyphenylpyruvate (4-HPP) were also identified.…”
Section: In Vitro Culture In Cannabismentioning
confidence: 99%
“…Similar findings have been shown by Ansari et al [46], where transformed hairy root culture of Ligularia fischeri were characterized by increased synthesis of phenolic compounds and higher radical scavenging activity, than control plants. Moreover, Cannabis sativa cell suspension culture treated with jasmonates and some precursors of phenylpropanoid pathway accumulated more phenolic derivatives and had increased radical scavenging activity against DPPH [47].…”
Section: Impact Of Biotic Elicitation On Biological Properties Of D mentioning
confidence: 99%
“…Plant cell culture, on the other hand, is introduced as a potential alternative to up-scale production of SMs in a shorter time and less space than traditional manners [ 7 ]. Moreover, a higher level of SMs production of different medicinal plants through cell culture has already been reported [ 8 , 9 ], although the production level of SMs through cell culture is still considerably lower than the intact plant in some cases. Particular substances called “elicitors” are applied as stress agents to boost the SM production in cultured plant cells [ 10 ].…”
Section: Introductionmentioning
confidence: 99%